SINGLE BURR-HOLE EVACUATION OF CHRONIC SUBDURAL HAEMATOMA - USE OF DRAINS VERSUS NO DRAINS - Bangash, Khurshid Ali; Munir, Aslan Javed; Khan, Habib Ullah (Pakistan Armed Forces Medical Journal, 2020)
Objective: To compare the use of drain insertion into the subdural space with no drains after burr-hole drainage of chronic subdural haematoma (CSDH) in terms of recurrence and neurological outcomes and complications. Study Design: Randomised controlled trial. Place and Duration of Study: The study was of 2 years duration conducted at neurosurgical unit Combined Military Hospital (CMH) Rawalpindi from Nov 2009 to Sep 2011. Material and Methods: A total of 72 patients were randomly assigned to two treatment groups, group 1 (n=36) were subjected to burr hole craniotomy with use of drains and group 2 (n=36) were subjected to no drains. The results were assessed at 3 months intervals in terms of recurrence and neurological outcomes and complications. Results: In this study recurrence was 8.3% with the use of a drains and 28% with no drains (p< 0.00) after burrhole drainage of chronic subdural hematoma. The results of the study showed that a drain significantly reduced the probability of recurrence. No other factor had a significant association with recurrence. There was not much difference in complications associated with surgical procedure. Conclusion: The recurrence is significantly less with the use of a drains after burr-hole drainage of chronic subdural haematoma.